Nội dung bạn tìm "
Cho M = 8(x – 1)(x2 + x + 1) – (2x – 1)(4x2 + 2x + 1) và N = x(x + 2)(x – 2) – (x + 3)(x2 – 3x + 9) – 4x., Cho M = 8(x – 1)(x2 + x + 1) – (2x – 1)(4x2 + 2x + 1) và N = x(x + 2)(x – 2) – (x + 3)(x2 – 3x + 9) – 4x.
" có trong những liên kết dưới đây, nhấp chuột để xem chi tiết:Cho M = 8(x – 1)(x2 + x + 1) – (2x – 1)(4x2 + 2x + 1) và N = x(x + 2)(x – 2) – (x + 3)(x2 – 3x + 9) – 4x.Chọn câu đúng (Toán học - Lớp 8)
Nguyễn Thanh Thảo - 03/09/2024 11:05:22
Cho M = 8(x – 1)(x2 + x + 1) – (2x – 1)(4x2 + 2x + 1) và N = x(x + 2)(x – 2) – (x + 3)(x2 – 3x + 9) – 4x.Chọn câu đúng (Toán học - Lớp 8)
Đặng Bảo Trâm - 01/09/2024 21:57:32